Natural Product‐Based Fungicides Discovery: Design, Synthesis and Antifungal Activities of Some Sarisan Analogs Containing 1, 3, 4‐Oxadiazole Moieties. Issue 2 (9th January 2020) - Xu, Hongyu; Jia, Ao; Hou, Enhua; Liu, Zhiyan; Yang, Rui; Yang, Ruige; Guo, Yong
Abstract: A series of sarisan analogs containing 1, 3, 4‐oxadiazole moieties were synthesized by iodine‐mediated oxidative cyclization and screened in vitro for their antifungal activities at 50 μg/mL against five phytopathogenic fungi such as Valsa mali, Curvularia lunata, Alternaria alternate, Fusarium solani and Fusarium graminearum . 1, 3, 4‐Oxadiazole derivatives 7e, 7p, 7r, 7t and 7u exhibited potent and a broad spectrum of antifungal activities against at least three phytopathogenic fungi at the concentration of 50 μg/mL. Especially, compound 7r displayed more potent antifungal activities against five phytopathogenic fungi than the positive control hymexazol. The EC50 of 7r against V. mali, C. lunata and A. alternate were 12.6, 14.5 and 17.0 μg/mL, respectively. Additionally, some interesting results of structure‐activity relationships (SARs) were also observed. Abstract :